Canine Silica Urolithiasis in Mexico, Associated with the Concentration of Dissolved Silica in Tap Water - Claudia Iveth Mendoza-López; Javier Del-Angel-Caraza; María Alejandra Aké-Chiñas; Israel Alejandro Quijano-Hernández; Jody P. Lulich; María Vicenta Esteller-Alberich (Veterinary Medicine International, 2021)
Silica urolithiasis is infrequent in dogs, but in Mexico represents 12.9%. Our hypothesis is the consumption of high amounts of silicates in the diet, especially that dissolved in tap water. The objective of this study was to determine the concentrations of silica in the tap water in different geographical areas and their relationship with cases of silicate urolithiasis in dogs. From 179 cases of silicate urolithiasis, 98.9% were from dogs within a geographic area called the Trans-Mexican Volcanic Belt, which represents a cross shaft to the center of the country. Silica concentrations in tap water ranged between 3 and 76 mg/L, with a range of 27 to 76 mg/L, a mean of 49.9 ± 12 mg/L within the Trans-Mexican Volcanic Belt, and a concentration from 3 to 30 mg/L, with a mean of 16.4 ± 7 mg/L outside this area; these were significantly different (p<0.001). These findings demonstrate that there is a geographic risk factor for silicate urolithiasis in urolith-forming dogs, related to the consumption of tap water with a high concentration of silica. Further studies are necessary to identify this same pathophysiological association in other species.